Coloring Arts Learning to Improve the Achievement of Mentally Disabled Children at Sumber Dharma Special School Malang City - Novianti, Ranti; Musdayanti, Linda Tri; Atmajaya, Silvia; Ansandyu, Bihard Riz (Proceedings Series of Educational Studies, 2024)
Coloring learning for mentally retarded children at SLB BCG Sumber Dharma Malang City is an important part of inclusive education aimed at stimulating creativity and developing their fine motor skills. This study aims to explore effective coloring learning methods in this special education environment. This research method uses a qualitative approach with data collection techniques through participatory observation and documentation of learning activities. The findings of the study indicate that coloring learning at SLB BCG Sumber Dharma is specifically designed to meet the needs of mentally retarded students. An inclusive and student-centered learning approach is the main focus, with the use of various media and techniques that are tailored to the child's individual abilities. Social interaction in small groups is also promoted to improve their social skills and self confidence. The results of the study indicate that the development of a more inclusive learning strategy for students with special needs through coloring learning at SLB BCG Sumber Dharma Malang City makes an important contribution to the development of their creative and fine motor potential. With a student-centered approach and a supportive environment, mentally retarded students can achieve success in learning and reach their full potential Keywords: Coloring Learning, Mentally Disabled, Special School